(untitled) (Research, Society and Development, 2021)
Parkinson’s disease is a pathology that arises among elderly individuals and causes a series of physical disorders that influence activities of daily living, such as eating. The present study aimed to map and analyze experimental research involving the evaluation of adapted artifacts that aid in the process of feeding people with Parkinson’s Disease, based on a Systematic Literature Review (SLR). The research was carried out in three databases: Scopus, Web Of Science and Science Direct, using different search strings. Three hundred and ninety (390) articles were initially found, and after the application of specific criteria, five (5) articles were analyzed. The results answered the research question and objectives of the review, as well as identified gaps related to the development and analysis of adapted cutlery, especially in the area of Product Design. As a limitation, the low production related to the theme was listed, as well as the use of approaches that are not directed to the problem and to the user’s point of view.